Growth form matters – Crustose lichens on dead wood are sensitive to forest management - Kantelinen Annina; Purhonen Jenna; Halme Panu; Myllys Leena (Elsevier B.V., 2022)
Lichens have a vital role in forest ecosystems and they are a threatened group in boreal forests. However, the conservation ecology of the total lichen community has very rarely been studied. Here we studied lichen species and communities, including macrolichens (=foliose and fruticose growth forms) and rarely studied crustose lichens, on decaying wood in boreal spruce-dominated forests in Finland. We also studied obligate lignicoles that grow only on dead wood and are mostly crustose in growth form. Species richness and community composition were examined on decaying logs and natural or cut stumps of Picea abies at different decay stages (2–5) in 14 stands, half of which were natural or seminatural and half recently managed. We used thorough search to yield a species list as close to complete as possible. Our study questions were: 1) Are species richness and lichen communities different in natural and managed forests, and if so, are there differences between macrolichens, crustose lichens and obligate lignicoles in how they respond to forest management? 2) How does the decay stage and dead wood type affect the lichens, i.e. are there differences between stumps and logs? We found a total of 127 lichen species. Most (75 %) of the recorded lichen species were crustose. With a generalized linear model we found that crustose lichens and obligate lignicoles had a higher species richness in natural than managed forests, but macrolichen richness was not significantly affected by forest management. Utilizing non-metric multidimensional scaling we discovered that site level community composition of macrolichens, crustose lichens and obligate lignicoles was also significantly different between natural and managed forests. We found that on dead wood unit level the decay stage had a significant effect on species richness and community composition, so that the species richness of all studied groups declined during the decay process. The dead wood type (stump vs log) had a significant effect on species richness of macrolichens and obligate lignicoles, both for which species richness was higher on logs than on stumps, as well as on the communities of crustose lichens.